The economic and societal burden of excessive daytime sleepiness in patients with obstructive sleep apnea. (June 2020) - Léger, Damien; Stepnowsky, Carl
Summary: Excessive daytime sleepiness (EDS) is common in patients with obstructive sleep apnea (OSA) and continues to persist in many patients despite adequate OSA treatment. EDS in OSA is associated with decreased quality of life (QOL) as well as increased societal burden, which may impact health care utilization and costs. However, economic burden is often not the primary focus in the treatment of EDS in OSA. This targeted literature review aimed to examine the published literature on the economic burden of EDS in OSA. This review identified available literature using a targeted PubMed search strategy using search terms related to EDS in OSA in adults. Results demonstrate that there are few studies that detailed the direct costs associated with EDS in OSA, though several studies indicated an association between EDS in OSA and indirect economic burdens, including motor vehicle accidents (MVAs), near misses, work productivity, mood, and QOL. Data from the literature confirmed that persistent EDS in OSA following continuous positive airway pressure persists in 12%–65% of patients. Future studies should further describe the direct costs of EDS in OSA, quantify the cost associated with MVAs and lost work productivity, and detail QOL and social impacts of the condition.